The Birth of New Jazz: How Progressive Musical Ideas Influenced Jazz Beyond its Sonic Elements (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2021)
The 1960s marked a major turning point in jazz. The albums So What, Time Out, and Mingus Ah Um, incorporated new musical ideas in response to the wave of post-bebop musicians. At the same time, the fight for Civil Rights continued to spread its influence across America, seeping into the compositions of many jazz musicians. The previously-mentioned records were not only influenced by their sonic novelties, but also by the social change taking place. For additional context, listen to the author's reflection on the piece below.